Effects of variable resistance training within complex training on strength and punch performance in elite amateur boxers - Liu, Yongfu; Huang, Zijing; Zhou, Zixiang; Zhang, Liqin; Guo, Yuqiang; Chen, Chao (Frontiers in Physiology, 2024)
Objectives This study explored the effects of 6 weeks of variable resistance training (VRT) and constant resistance training (CRT) within complex training, on muscle strength and punch performance. Methods Twenty-four elite female boxers from the China National team were divided randomly between an experimental group (VRT) and a control group (CRT). Maximum strength of the upper and lower limbs, countermovement jump (CMJ) performance, and punch performance (single, 10s and 30s continuous) were assessed pre- and post- intervention. Results VRT and CRT showed significant increases (p < 0.001) in the bench press (ES = 1.79 and 1.07, respectively), squat (ES = 1.77 and 1.10, respectively), and CMJ (ES = 1.13 and 0.75, respectively). The bench press (p < 0.05) and squat (p < 0.05) improved significantly more following VRT compared to CRT. Additionally, single punch performance (speed, force, and power) increased significantly in the experimental group (ES = 1.17–1.79) and in the control group (ES = 0.58–1.32), except for the lead punch force in the control group (p > 0.05, ES = 0.20). 10s continuous punch performance (number, speed, force, and power) increased significantly (both p < 0.05) in the experimental group (ES = 0.52–1.65) and in the control group (ES = 0.32–0.81). 30s continuous punch performance (number, force, and power) increased significantly increased significantly (both p < 0.05). However, no statistically significant differences were found between groups for punch performance. Conclusion These findings provide evidence that VRT may improve maximum muscle strength in both upper and lower limbs, vertical jump and punch performance in elite amateur boxers.